Republic of Yemen : 2007 Article IV Consultation; Staff Report; Staff Supplements; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Yemen. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This 2007 Article IV Consultation highlights that despite recent progress in poverty reduction, Yemen remains far from achieving the Millennium Development Goals. Oil production has been declining since 2000, and in the absence of major discoveries, proven oil reserves could be depleted in some 10 years' time. Economic performance in 2006 was generally favorable, but was accompanied by an increase in inflation. Overall real GDP growth reached 4 percent in 2006, with a 6 percent non-oil growth offsetting an 8 percent decline in oil production.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet